Structure-function relationships underlying GluA2 mechanisms of deactivation, desensitization, and modulation - Harms, Jonathan E., author; Partin, Kathryn M., advisor; Amberg, Gregory C., committee member; Prasad, Ashok, committee member; Tamkun, Michael M., committee member (Colorado State University. Libraries, 2013)
Glutamate is the primary excitatory neurotransmitter in the central nervous system, where it is principally responsible for mediating excitatory neurotransmission. Ligand-gated receptors to glutamate, such as the a-amino-3-hydroxy-5-methyl-isoxazole-propionic acid (AMPA) receptor, are responsible for many cognitive processes; with the AMPA receptor showing an essential role in learning, memory, and synaptic plasticity. As many mental illnesses and diseases show underlying cognitive complications, therapeutic drugs that can alleviate these cognitive deficits show tremendous potential benefit. However, despite great interest and continued advancement, progress of drugs through clinical trials into available treatments has been slow and problematic. One potential reason for the slow progress of drug development is a lack of basic understanding for how compounds bind to AMPA receptors and upregulate their function. Presented here are several studies aimed to better understand how structural interactions regulate AMPA receptor mechanisms of gating and modulation. These studies combine fast-perfusion electrophysiology capable of simulating synaptic events with structural information obtained from x-ray crystallography studies to analyze potential mechanisms of allosteric modulation. Promisingly, we have identified potential patterns relating modulator properties such as size and rigidity with their observed physiological effects. Such patterns suggest that information from these studies can facilitate design of more targeted and efficacious cognition enhancing drugs. In addition to this drug analysis, we identify a new potential drug target site: the AMPA receptor outer vestibule near the ion-conducting pore. We further characterize that alteration to this site acts independently of other modulators, providing a site for modulators that may accompany current pharmacological therapies. Together, these studies demonstrate that structural information can be successfully applied to the process of drug design, with the added benefit of enhancing our understanding for molecular mechanisms of AMPA receptor function.
Keywords: AMPA receptor; kinetic model; glutamate; deactivation